Effects of antitumor derivatives of ineffective transplatin on bacterial cells: Is DNA a pharmacological target - Kasparkova, Jana; Brabec, Viktor (Journal of inorganic biochemistry, 2015)
The effects of the two representatives of the antitumor transplatinum agents, trans-[PtCl2(methylamine)2] and trans-[PtCl2(NH3)(1-methyl-7-azaindole)] on bacterial growth were examined. The results show that these antitumor transplatinum agents can be grouped with the coordination Pt(II) compounds exhibiting antitumor activity and capable of inducing bacterial filamentation and initiate lysis in lysogenic bacteria. The results corroborate the thesis that DNA is the potential cellular target also for a class of antitumor derivatives of transplatin.
Keywords: organoplatinové sloučeniny; Organoplatinum Compounds; protinádorové látky; DNA bakterií; Escherichia coli; Antineoplastic Agents; cisplatina; DNA, Bacterial; Cisplatin